SMITH-LEMLI-OPITZ SYNDROME. CASE REPORT - Sorin Ioan Iurian; Livia Ognean; Han Brunner; Leo Kluijtmans; Petr Jira; Dana Fintina; Bogdan Ionut Mehedintu (Amaltea Medical Publishing House, 2015)
Smith-Lemli-Opitz syndrome (SLOS) is an autosomal-recessive inherited disease characterized by multiple anomalies secondary to cholesterol synthesis impairment. The authors present diagnosis peculiarities and limitation of treatment options in a 5-weeks old infant with ambiguous genitalia.